Migrasi Pekerja 'Metu' di Desa Patokpicis Kecamatan Wajak Kabupaten Malang: Migration of 'Metu' Workers in Patokpicis Village, Wajak District, Malang Regency - Ahmad Junaidi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
-Upon closer observation, the rapid population growth in the Malang region is not solely due to birth rates but also urbanization factors. Urbanization, as agreed upon by experts, is one way to alter one's status. This is because the trade exchange value of the rural agricultural sector, including wage levels for minimally land-owning farm laborers, is far lower than in urban areas. The density of urban populations is further evident due to the influx of migrant workers employed across various sectors. These migrant workers typically originate from villages surrounding the city. Migrant workers or